Landscape and human settlement dynamics in insular environments : an archeological approach - Mansur, Maria Estela; Hardy, Karen; Piqué, Raquel
Archaeological research at opposite ends of the planet in subarctic and subantarctic island regions have proceeded largely independently of each other. This has resulted in the development of independent interpretive frameworks to explore the dynamics of past human settlement, particularly with regard to hunter-gatherer societies. In the northern hemisphere, archaeological studies are part of the European Paleeolithic / Mesolithic research tradition, which has a largely terrestrial focus. Although in recent years new emphasis has been placed on research in coastal areas, including the subarctic area, theoretical frameworks remain similar to those employed in the study of hunter-gatherers of the inland areas of continental Europe. At the other end of the planet, Tierra del Fuegian archaeology is closely connected with ethnoarchaeology in which archaeological data is imbued with ethnographic and ethnohistorical perspective based on extant records as native populations still lived there until the end of XIXth century. This has resulted in an emphasis on social processes. We believe that the ethnoarchaeological-based models which utilise this broader perspective on aboriginal strategies, constitute an excellent starting point to address some aspects of Scottish mesolithic archaeology. We have adopted a comparative approach, and we have used the differences in scales of analysis (environment, home ranges, etc.) as our starting point. In this paper we highlight some of the comparable features and offer a new perspective on the archaeological record and mobility of hunter-gatherer sites in Scotland using the ethnohistorical records from Tierra del Fuego. Fil: Mansur, Maria Estela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Hardy, Karen. Universitat Autonoma de Barcelona; España Fil: Piqué, Raquel. Universitat Autonoma de Barcelona; España